2015
DOI: 10.1097/htr.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Related Harms Among Adolescents With and Without Traumatic Brain Injury

Abstract: There are strong and demographically stable associations between TBI and substance use. These associations may not only increase the odds of injury but impair the quality of postinjury recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 57 publications
6
53
1
Order By: Relevance
“…1-2 Greater effort to track concussions using large-scale epidemiological data is needed to identify high-risk subpopulations and monitor prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-2 Greater effort to track concussions using large-scale epidemiological data is needed to identify high-risk subpopulations and monitor prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…A regional study of Canadian adolescents suggests that approximately 20% have sustained a concussion. 1-2 Providing a national baseline of concussion prevalence and correlates is necessary to target and monitor prevention efforts to reduce these types of injuries during this important developmental period. To address this gap we examined the prevalence and correlates of self-reported diagnosed concussions using a national sample of U.S. adolescents.…”
mentioning
confidence: 99%
“…In fact, estimates indicate that 37–66% of TBI patients struggle with alcohol use disorders, while 10–44% of TBI patients abuse illicit drugs 5 . Notably, within illicit drug use, studies have shown that TBI patients are most likely to abuse cannabis, cocaine, methamphetamine, and prescription medications, including opioids, stimulants, benzodiazepines, antidepressants, and antipsychotics 610 . Furthermore, additional studies have shown that daily cigarette use is significantly elevated in TBI patients when compared to age-matched controls, suggesting that brain injuries may also affect nicotine-dependence 6, 11 .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Adolescents who had experienced one or more TBIs in their lifetime had odds twice as much to screen positive for current hazardous drinking or for reporting binge drinking in the past 12 months compared to those who never had a TBI. 20 TBI and hazardous drinking are relatively common among adolescents 4 19 20 and they have been linked with poor academic performance and mental health issues, including suicide, and increased violent and non-violent conduct behaviours. 19 24-29 Several studies using imaging methods have noted negative additive effects of alcohol misuse and TBI, such as brain atrophy over time and reduced reaction times.…”
Section: Introductionmentioning
confidence: 99%